2015
DOI: 10.1289/ehp.1408989
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S and F: A Systematic Review and Comparison of the Hormonal Activity of Bisphenol A Substitutes

Abstract: BackgroundIncreasing concern over bisphenol A (BPA) as an endocrine-disrupting chemical and its possible effects on human health have prompted the removal of BPA from consumer products, often labeled “BPA-free.” Some of the chemical replacements, however, are also bisphenols and may have similar physiological effects in organisms. Bisphenol S (BPS) and bisphenol F (BPF) are two such BPA substitutes.ObjectivesThis review was carried out to evaluate the physiological effects and endocrine activities of the BPA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
660
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,164 publications
(727 citation statements)
references
References 75 publications
16
660
3
5
Order By: Relevance
“…Bisphenol S (BPS) and Bisphenol F (BPF) are the main substitutes of BPA 168. They were considered “safer” alternatives to BPA due to their stability against high temperature and resistance to sunlight 169.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol S (BPS) and Bisphenol F (BPF) are the main substitutes of BPA 168. They were considered “safer” alternatives to BPA due to their stability against high temperature and resistance to sunlight 169.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both phthalates and BPA are considered endocrine modulating chemicals: phthalates are believed to function as antiandrogens, while BPA may act as an estrogen, anti-estrogen, androgen, or antiandrogen. 41,42 This result could be interpreted as increased BPA levels in ADHD affecting neuronal connectivity, synaptic function, and dendritic length by effects on estrogen and androjen. Also, this result could be accepted in line with the suggestion that BPA acts via estrogen receptors to alter dopamine signaling, leading to hyperactivity and attention deficits in humans.…”
Section: ____________________________________________________________mentioning
confidence: 93%
“…Some of the chemicals such as bisphenol F (BPF) and bisphenol S (BPS) are generally used as alternatives in consumer products and labelled as 'BPA-free'. Rochester and Bolden 31 reviewed the toxicity of about 20 chemicals that are suggested as BPA-alternatives in 2015. They concluded that these compounds are also equally potent as BPA and exhibit endocrine disrupting effects.…”
Section: History Of Bpamentioning
confidence: 99%